Spectrophotometric Determination of Copper in Serum Using 6-(2-Naphthyl)-2,3-dihydro-1,2,4-triazine-3-thione - BARAZANDEH TEHRANI*, MALIHEH; FAZEL SHAMSA, S.; SHAMS†, SEDIGHE; MASTARI FARAHANI, MOHSEN (Asian Journal of Chemistry, 2009)
A simple and accurate spectrophotometric method for determination of copper in serum using 6-(2-naphthyl)-2,3-dihydro-1,2,4-triazine-3-thione (NDTT) has been described. This method is based on the formation of a red coloured complex of copper with a reagent, 6-(2-naphthyl)-2,3- dihydro-1,2,4-triazine-3-thione. The pink coloured Cu-NDTT complex was soluble in chloroform and showed maximum absorbance at 314 nm. In this study, derivative spectrophotometric method is proposed for determination of Cu(II) in serum based on the reaction between copper and new chromogenic compound NDTT. Serum was first treated with trichloroacetic acid for deproteination and ascorbic acid to release Cu from protein. After addition of tartaric acid and NDTT, complex was extracted by chloroform. The optimum reaction conditions and other important analytic parameters have been investigated. Beer's law was obeyed in the copper concentration range of 0.5-6 μg mL-1 of serum and the detection limit was 0.106 μg. The linear regression equation was A = 0.04507C–0.0001. The within-day and between-day variations in four selected concentration (0.5, 1, 4, 6 μg/mL) were less than 2.68 and 3.07 %, respectively. The procedure was validated by analyzing control serum samples. The results were in good agreement with the concentration range of copper in the control serum done by atomic absorption. The method was applied to human serum samples with satisfactory results. The proposed method was simple, selective and sensitive for determination of copper in serum.